Probabilistic Modelling of Bridge Safety Based on Damage Indicators. (2016) - Heitner, Barbara; OBrien, Eugene J.; Schoefs, Franck; Yalamas, Thierry; Décatoire, Rodrigue; Leahy, Cathal
Abstract: This paper introduces the various aspects of bridge safety models. It combines the different models of load and resistance involving both deterministic and stochastic variables. The actual safety, i.e. the probability of failure, is calculated using Monte Carlo simulation and accounting for localized damage of the bridge. A possible damage indicator is also presented in the paper and the usefulness of updating the developed bridge safety model, with regards to the damage indicator, is examined.